If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2 + -3x) = -5(x + -3) (2 * 2 + -3x * 2) = -5(x + -3) (4 + -6x) = -5(x + -3) Reorder the terms: 4 + -6x = -5(-3 + x) 4 + -6x = (-3 * -5 + x * -5) 4 + -6x = (15 + -5x) Solving 4 + -6x = 15 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 4 + -6x + 5x = 15 + -5x + 5x Combine like terms: -6x + 5x = -1x 4 + -1x = 15 + -5x + 5x Combine like terms: -5x + 5x = 0 4 + -1x = 15 + 0 4 + -1x = 15 Add '-4' to each side of the equation. 4 + -4 + -1x = 15 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 15 + -4 -1x = 15 + -4 Combine like terms: 15 + -4 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| X+10+x=34 | | 8x-4+6=7x+1 | | 57t-39-(90+45)= | | 5x+2+3x=66 | | -1-(-1)= | | 12x-3=13x | | X-12=-27 | | 6x+4+4x=74 | | 8(a+7+6b)= | | 9x-8w= | | 10m+2n-6m+8n= | | 7+5x+5x=7 | | 5x+2+4x=56 | | X+3+4x=33 | | 2x+3=3x-4 | | 66=7x+7x+10 | | 2x-6=4x | | 10x+7=9(5-x) | | 6(m-9)=25 | | 5x+1+6x=1 | | 4x+15=75 | | 10f+(3f+2)=30 | | -11-9=x | | 6x-4x+4x=18 | | 2x+12=180 | | 2x-5=27 | | -2x-5=11 | | -2-5=11 | | -5q+5=-15 | | 5x+3x+2x=10 | | 3y+20=180 | | 9x+4=30x-8 |